Vascular flora of Southern Brazilian outcrops associated with Atlantic Forest: small relict environment that needs to be preserved - Monteiro-Ré, Tatiane (2022)
The rocky outcrops in the municipality of Campo Mourão (Paraná State) are all surrounded by remaining Atlantic Forest, unlike the typical outcrops associated with river courses, fields, or hilltops. Because it is such specific vegetation, it is essential to record the floristic composition, verifying only species and the conservation status of local populations. This study cataloged the species of vascular plants occurring in four rocky outcrops areas of Campo Mourão: Nishida outcrop (1,808 ha); Bica do Rio do Campo outcrop (0.458 ha); Perdoncini outcrop (0.228 ha), and Lago Azul State Park outcrop (0.021 ha). A total of 203 collections were analyzed, representing 152 species (eight exotic to Brazil), distributed in 66 families and 135 genera. The more richness families were Poaceae, Asteraceae, Fabaceae, Rubiaceae, and Bromeliaceae. The predominant life form was herbs and shrubs, and most species are terrestrial and rupicolous. The rocky outcrops of Campo Mourão, despite the small total area (25,150 m2), have 10 % of the exclusive species in the municipality. Also, 14 species are endemic in Brazil, and two are endemic in Paraná, being Portulaca hatschbachii (Portulacaceae) officially threatened to extinction in Brazil. In these areas, several species found have been little collected in Paraná State and Brazil, in addition to the presence of life forms adapted to survival on the exposed rock. This demonstrates that despite being small, these sites are critical environments for preserving biodiversity in the region.